Analisa Kadar Logam Berat Merkuri (Hg) Pada Krim Pemutih Yang Beredar Di Daerah Percut Sei Tuan Sampali Secara Spektrofotometri Serapan Atom (SSA) - Tisna Harmawan; Ade Irmawati (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Several researches have been conducted about "Analysis of Heavy Metal Content Mercury (Hg) On Whitening Face Cream Circulating On Percut Sei Tuan Sampali area with Atomic Absorption Spectrophotometer (AAS)". The research study was run at the Health Central Laboratory of North Sumatra. This study aimed to determine the levels of mercury (Hg) in the whitening face creams that ciirculating in the Percut Sei Tuan Sampali district. It also need to determine the levels of mercury (Hg) from Percut Sei Tuan Sampali area that accordance with the Regulation No. HK.03.1.23.07.11.6662 POM. However, this was an experiment study with a random of 5 samples among the whitening face cream at Percut Sei Tuan Sampali area. Thus, this area presented that the heavy metal mercury (Hg) from 5 samples were obtained the results that samples 1A was 1.5429 mg / L, samples 2A is 1.5334 mg / L, samples 3A is 1.4851 mg / L, samples 4A is 1.4916 mg / L, the sample 5A is 1, 5180 mg / L. However, the results showed that the mercury (Hg) value was above the levels was determined by BPOM RI, (the permission terms of heavy metal contamination Mercury (Hg) 1 mg / L No. HK.03.1.23.07.11.6662 in 2011). Thus, it was necessary to supervise the facial whitening cream in the Percut Sei Tuan Sampali society.